1986
DOI: 10.1111/j.1476-5381.1986.tb10261.x
|View full text |Cite
|
Sign up to set email alerts
|

Probenecid potentiates the hyperglycaemic effect but reduces the diuretic effect of frusemide in mice

Abstract: 1 The effect of probenecid on frusemide-induced diuresis and hyperglycaemia was studied in mice. 2 Probenecid, a known inhibitor of tubular secretion of organic anions in the kidney, strongly reduced the diuretic response to frusemide (25 or 200 mg kg-' body weight). This effect of probenecid appeared to be dose-dependent up to 240 mg kg-' body weight, at least at the lower concentration of frusemide. 3 Pretreatment with probenecid (240 mg kg-' body weight) potentiated the hyperglycaemic effect of frusemide (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In order to elucidate the mechanisms behind the diabetogenic effect of the loop diuretic furosemide, we have previously studied its effect on the carbohydrate metabolism in adult lean as well as obese-hyperglycaemic mice (ob/obmice) (Sandstrom 1987;Sandstrom & Sehlin 1988a & b). We found that a single injection of furosemide (200 mg/kg body weight) induced acute hyperglycaemia in both mouse strains but that long-term glucose intolerance developed only in ob/ob-mice (Sandstrom 1987;Sandstrom & Sehlin 1988a & b). This made in tempting to speculate that the inheritance of the ob/ob genome, as such, is linked to the susceptibility to develop disturbed carbohydrate metabolism after furosemide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to elucidate the mechanisms behind the diabetogenic effect of the loop diuretic furosemide, we have previously studied its effect on the carbohydrate metabolism in adult lean as well as obese-hyperglycaemic mice (ob/obmice) (Sandstrom 1987;Sandstrom & Sehlin 1988a & b). We found that a single injection of furosemide (200 mg/kg body weight) induced acute hyperglycaemia in both mouse strains but that long-term glucose intolerance developed only in ob/ob-mice (Sandstrom 1987;Sandstrom & Sehlin 1988a & b). This made in tempting to speculate that the inheritance of the ob/ob genome, as such, is linked to the susceptibility to develop disturbed carbohydrate metabolism after furosemide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furosemide causes disturbed carbohydrate metabolism also in laboratory animals (Foy 1967;Wales et a/. 1968;Aynsley-Green & Alberti 1973;Foy & Furman 1971, 1972Sandstrom 1987;Sandstrom & Sehlin 1988a &. b).…”
mentioning
confidence: 99%
“…The ability of probenecid to completely block the natriuretic and diuretic actions of frusemide in the dog has never been demonstrated in man (Chennavasin et al, 1979;Homeida et al, 1977;Honari et al, 1977). Further examples of inter-species differences are that probenecid blocks the diuresis induced by frusemide, but not by bumetanide, in the cat (Friedman & Roche-Ramel, 1977), and in mice probenecid appears to cause dose-dependent reductions in frusemide-induced diuresis (Sandstrom, 1986). In man probenecid decreases the renal clearance of frusemide by a third (present study) to a half (Chennavasin et al, 1979).…”
Section: Discussionmentioning
confidence: 99%